Comparison Of Surgical Excision Of Lower Lip Mucocele Vs Intralesional Dexamethasone Injection - Piracha, Adia Bushra; Chaudhry, Sadia; Masood, Sundas; Javaid, Amna; Afzal, Muhammad; Umara, Ansa (Journal of Rawalpindi Medical College, 2026)
Objective: Mucocele is a benign, mucus containing cystic lesion of minor salivary glands. The objective of this study was to compare the outcomes of surgical excision versus corticosteroid in the management of oral lower lip mucocele. Methods: One hundred thirty patients with lower lip mucocele of variable size (5mm to 18mm)were included. Group A patients had surgical excision while group B patients received corticosteroid treatment. Patients were allocated using blocked randomization. Outcomes in both groups were assessed using Chi Square test. Results: Mean age in group A was 32±7.68 years while 31.49±8.92 years in group B. Postoperative pain was notably reduced in group B (Corticosteroid) at the 3rd postoperative day, mucocele swelling at the 3rd and 7th day was significantly lower in group B, however, no notable difference was seen in wound dehiscence in both groups on the 3rd and 7th postoperative day. Conclusion: The results of this study showed that corticosteroid therapy was notably effective than surgical excision for the management of oral mucocele in terms of postoperative pain and mucocele swelling. Keywords: Mucocele, Surgical excision, Comparison, Postoperative pain, Swelling, Wound dehiscence